(3x-2)(5x+1)(4)=

Simple and best practice solution for (3x-2)(5x+1)(4)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3x-2)(5x+1)(4)= equation:


Simplifying
(3x + -2)(5x + 1)(4) = 0

Reorder the terms:
(-2 + 3x)(5x + 1)(4) = 0

Reorder the terms:
(-2 + 3x)(1 + 5x)(4) = 0

Reorder the terms for easier multiplication:
4(-2 + 3x)(1 + 5x) = 0

Multiply (-2 + 3x) * (1 + 5x)
4(-2(1 + 5x) + 3x * (1 + 5x)) = 0
4((1 * -2 + 5x * -2) + 3x * (1 + 5x)) = 0
4((-2 + -10x) + 3x * (1 + 5x)) = 0
4(-2 + -10x + (1 * 3x + 5x * 3x)) = 0
4(-2 + -10x + (3x + 15x2)) = 0

Combine like terms: -10x + 3x = -7x
4(-2 + -7x + 15x2) = 0
(-2 * 4 + -7x * 4 + 15x2 * 4) = 0
(-8 + -28x + 60x2) = 0

Solving
-8 + -28x + 60x2 = 0

Solving for variable 'x'.

Factor out the Greatest Common Factor (GCF), '4'.
4(-2 + -7x + 15x2) = 0

Factor a trinomial.
4((-1 + -5x)(2 + -3x)) = 0

Ignore the factor 4.

Subproblem 1

Set the factor '(-1 + -5x)' equal to zero and attempt to solve: Simplifying -1 + -5x = 0 Solving -1 + -5x = 0 Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + -5x = 0 + 1 Combine like terms: -1 + 1 = 0 0 + -5x = 0 + 1 -5x = 0 + 1 Combine like terms: 0 + 1 = 1 -5x = 1 Divide each side by '-5'. x = -0.2 Simplifying x = -0.2

Subproblem 2

Set the factor '(2 + -3x)' equal to zero and attempt to solve: Simplifying 2 + -3x = 0 Solving 2 + -3x = 0 Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -3x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -3x = 0 + -2 -3x = 0 + -2 Combine like terms: 0 + -2 = -2 -3x = -2 Divide each side by '-3'. x = 0.6666666667 Simplifying x = 0.6666666667

Solution

x = {-0.2, 0.6666666667}

See similar equations:

| 6+3q=15 | | 6=10-2w | | 5a-2b-8b+6a= | | 3-2r=2r | | 8x+14+2x=40-(9x+3) | | 2k-4=4 | | 2k-4= | | -10+7(a+3)=4(a-1)+5 | | f(-5)=0 | | 3x+22=4(x-1)-1 | | 1/7w=11 | | (-5)+(-7)= | | 3.67-(5.73+3)= | | 2(3x-5)=-7 | | 4x+7x=3x+5 | | 12x+8y=-1 | | 11x+7x+19=56 | | 10-2x-1= | | T^2-41=0 | | 5[3a-2a(3a+6b)+6a^2]= | | x-2y-3x+4y= | | 6+5y-3=9y+27-7y | | -6.58+12=-5.42 | | -2x-3(X+5)=14 | | 2[5(x+y)-2(3x-4y)]= | | 7x=90+x | | 2x+95=6x+65 | | x*x-x+6=0 | | 4(t-4)+6t=5(2t+2)-9 | | 2x+10=4+1 | | x^2-2500= | | 3r-15=2r+10 |

Equations solver categories